Improving health and social care services for slum-dwelling older adults: Perspectives of health professionals - Attafuah, Priscilla Yeye Adumoah; Everink, Irma H. J.; Lohrmann, Christa; Abuosi, Aaron Asibi; Schols, Jos M. G. A. (Frontiers in Public Health, 2022)
Background: Besides confronting the challenges of a growing older population, developing countries are dealing with limited resources and infrastructure, to ensure good health and social care services. One of these developing countries facing these challenges is Ghana. The healthcare system in Ghana currently does not have specialized geriatric services and is funded through the National Health Insurance Scheme (NHIS), private insurance companies and an out-of-pocket expenditure system. Social care services are important in improving Quality of Life (QoL) as it helps in building and strengthening relationships while also keeping slum-dwelling older adults active. There are various challenges with the health and social care of older adults in slums and practical ways to improve these have not been explored among the providers of this care. Aims: This study, therefore, aims aimed to explore 1) the views of health professionals on older slum-dwelling adults' health and social care needs, access, and use; and 2) recommendations for improving access to health and social care services among slum-dwelling older adults. Method: A qualitative exploratory descriptive approach was used among health professionals by conducting a focus group discussion (FGD) and interviews. A semi-structured interview guide was used to collect data from each participant. Results: A total of 27 participants took part in the study. In the analysis of transcripts, three themes and fourteen subthemes were conceptualized. Financial difficulties, queueing issues, distance to health facilities, health illiteracy and negative attitude of health professionals were identified as some barriers to the utilization of formal healthcare services. Social care services were described as non-existent, not structured, and having limited resources to cater for attendants. The health professionals also provided recommendations for improvement. Conclusion: Health professionals in this study discussed barriers to access and use of health and social care services. Addressing these barriers is essential to improve the use of formal health and social care services and diminish health inequity among older adults.